Socio-Economic Factors and Women Participation in Rwandan Mining Projects a Case of Rwanda Mining Association - Mwambarangwe, Patricie; Shukla, Jaya (Journal of Advanced Research in Humanities and Social Sciences, 2020)
This report presents a study conducted in Rwanda Mining Association to assess socio-economic factors and women participation in Rwandan mining projects. Specific objectives for the study were: To investigate the effect of socio-cultural and economic factors on women participation in mining projects; Determine the influence of company management procedures on women participation in mining project; and to examine the impact of mine sites working and living conditions on women participation in mining projects. Using purposive and simple random sampling technique, the target population of 835 workers (676 men and 159 women) was selected from 30 mining companies. The sample size of 270 respondents including 51 women and 219 men was also selected. Collected data was analyzed through SPSS software using chi-square and regression models. It was found that socio-cultural beliefsand Socioeconomic factors have negative relationship with women participation in mining. Company management procedures (recruitment, workers’ promotion and skillsdevelopment and job allocation procedures) applied in human resources management were also found to have negative effect on women participation in mining. The nature of mining work places, working and living conditions in terms of Occupational Safety and Health (OSH) of workers do not facilitate women integration in mining. Female workers face particular challenges such as being fired once they get pregnant and lack of work contracts. If mining is to contribute for poverty alleviation by eliminating inequality in accessing economic benefits in rural areas between men and women, all these factors should be addressed in a manner favorable to women. It is recommended that Community should be sensitized on how to develop good understanding on social responsibilities between men and women by balancing gender principles with socio-cultural beliefs. Positive work environment for all workers, both men and women should be established and respect of rights accorded to women in terms of OSH should be ensured as it is done in other sectors of activities. How to cite this article: Mwambarangwe P, Shukla J. Socio-Economic Factors and Women Participation in Rwandan Mining Projects a Case of Rwanda Mining Association. J Adv Res Humani Social Sci 2020; 7(2): 9-19.